Gender-Stratified Analysis of Haitian Perceptions Related to Sexual Abuse and Exploitation Perpetrated by UN Peacekeepers during MINUSTAH - Luissa Vahedi; Heather Stuart; Stéphanie Etienne; Sabine Lee; Susan A. Bartels (Sexes, 2021)
Feminist scholarship has analyzed the gendered dynamics of national- and international-level risk factors for peacekeeper-perpetrated sexual exploitation and abuse (SEA); however, the gendered dynamics within the host country have not been adequately considered. Using the United Nations Stabilization Mission in Haiti (MINUSTAH) as a case study, this research analyzes gender differences within community-level perceptions of SEA. Using SenseMaker® as a data collection tool, cross-sectional qualitative and quantitative data were collected by Haitian research assistants over an 8-week period in 2017. Participants first shared a narrative in relation to MINUSTAH and then self-interpreted their narratives by noting their perceptions, attitudes, and beliefs on a variety of questions. The self-coded perceptions were analyzed quantitatively to determine patterns, and this was complemented with a qualitative analysis of the narratives. Women/girls were more likely to perceive the sexual interactions as “relationships” compared to Haitian men/boys. Furthermore, women/girls were more likely to perceive the peacekeeper as “supportive”, whereas men/boys conceptualized the peacekeeper as “authoritative”. SEA-related policies/programs, such as the UN Trust Fund in Support for Victims of SEA, should engage with local Haitian actors and consider such nuanced and gendered perceptions to maximize community trust and program efficacy.